Human induced pluripotent stem cell models for Alzheimer’s disease research: a bibliometric analysis - Sun, Yuning; Liu, Zhilong; Zhang, Zongbo; Kang, Yufeng; Wang, Xinlian; Zhang, Yiping; Liu, Yan; Zhao, Pei (Frontiers in Human Neuroscience, 2025)
IntroductionAlzheimer’s disease (AD), the leading cause of dementia, remains without adequate treatment. Current models do not fully replicate human physiology and pathology. The advent of human induced pluripotent stem cell (hiPSC) technology offers a novel approach to studying AD.MethodsOur study conducted a bibliometric analysis to assess the application and development of hiPSC technology in AD research. We retrieved 531 articles on hiPSC models of AD from the Web of Science Core Collection, published between January 2010 and June 2024. CiteSpace and VOSviewer were used to analyze authorship, geographic contributions, journal influence, and citation patterns.ResultsOur findings reveal a steady increase in publications over 14 years, with the United States leading in contributions, followed by China. Li-Huei Tsai from the Massachusetts Institute of Technology is a prominent researcher. PLoS One emerges as the most influential journal. Research trends have focused on inflammation, astrocytes, microglia, apolipoprotein E (ApoE), and tau.DiscussionBibliometric analysis is crucial in identifying research gaps and trends and guiding future studies to address unmet needs in understanding and modeling human physiology and pathology. Leveraging hiPSC models to investigate the molecular mechanisms of familial and sporadic AD is expected to provide a crucial foundation for developing future treatment strategies.ConclusionIn summary, the bibliometric findings from this study provide a comprehensive overview of the current research landscape in hiPSC models for AD. It also highlights emerging trends and research gaps, crucial for guiding future research efforts, particularly in exploring novel therapeutic targets and improving understanding of disease mechanisms.